Pipelines 2018. proceedings of sessions of the Pipelines 2018 Conference, July 15-18, 2018, Toronto, Ontario, Canada - Macey, Christopher C.; Lueke, Jason, S. (Online access: American Society of Civil Engineers (ASCE) American Society of Civil Engineers (ASCE) Conference Proceedings., 2018)
"This collection contains 87 peer-review papers on construction, condition assessment, and rehabilitation of pipelines. Topics include: risk-based asset management; pipeline coatings, linings, and corrosion; assessment and inspection techniques; failure evaluation and emergency repairs; rehabilitation techniques; and international case studies."--